Development of an Automated Information and Analytical System for Monitoring the Stock and Foreign Exchange Markets - Elena V. BUTSENKO; Aleksandr V. KURDYUMOV (Communications of International Proceedings, 2021)
The article presents the development of a computer information and analytical system designed to automate the functions of monitoring data on the stock and foreign exchange markets. The relevance of the article is due to the development of the information-digital economy and its influence on all spheres of human activity, including the securities market and the market for buying and selling foreign currency. The concept of developing a monitoring system, the process of selecting a database management system, as well as creating an interface for the monitoring system are presented. The process of forming a data monitoring dashboard is shown. The corresponding graphs and SQL queries have been built.
Keywords: Monitoring System; Stock Market; Foreign Exchange Market; Mysql; Navicat; Grafana; Dashboard; SQL Queries.